The effect of ICT learning media and discipline on the effectiveness of learning mathematics - Anggun Pastika Sandi; Handy Fernandy (International Journal of Trends in Mathematics Education Research, 2022)
This study aims to determine the effect of information computer technology (ICT)-based learning media and learning discipline on the effectiveness of mathematics learning process. The experi-ment was carried out in two groups where each group was given different treatments. The first group was taught using ICT-based learning media, while the second group was taught using conventional learning media. Each group was further divided into two categories according to their level of discipline, namely groups with high levels of discipline and groups with low levels of discipline. The method used in this research is an experiment with a treatment by level analysis model. The type of test used is Anova Two-Way. Based on the results of the analysis, it shows that the group taught using ICT-based learning media obtained a higher effectiveness of learning pro-cess than the group taught using conventional learning media. and groups that have a high level of discipline get a higher effectiveness of the learning process than groups with low levels of dis-cipline. and it is also evident that there is an influence of the interaction between the use of ICT-based learning media and the level of discipline on the effectiveness of learning process.